Use of gene therapy for optic nerve protection: Current concepts - Xu, Kexin; Yu, Lu; Wang, Zhiyi; Lin, Pei; Zhang, Ningzhi; Xing, Yiqiao; Yang, Ning (Frontiers in Neuroscience, 2023)
Gene therapy has become an essential treatment for optic nerve injury (ONI) in recent years, and great strides have been made using animal models. ONI, which is characterized by the loss of retinal ganglion cells (RGCs) and axons, can induce abnormalities in the pupil light reflex, visual field defects, and even vision loss. The eye is a natural organ to target with gene therapy because of its high accessibility and certain immune privilege. As such, numerous gene therapy trials are underway for treating eye diseases such as glaucoma. The aim of this review was to cover research progress made in gene therapy for ONI. Specifically, we focus on the potential of gene therapy to prevent the progression of neurodegenerative diseases and protect both RGCs and axons. We cover the basic information of gene therapy, including the classification of gene therapy, especially focusing on genome editing therapy, and then we introduce common editing tools and vector tools such as Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) -Cas9 and adeno-associated virus (AAV). We also summarize the progress made on understanding the roles of brain derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF), phosphatase-tensin homolog (PTEN), suppressor of cytokine signal transduction 3 (SOCS3), histone acetyltransferases (HATs), and other important molecules in optic nerve protection. However, gene therapy still has many challenges, such as misalignment and mutations, immunogenicity of AAV, time it takes and economic cost involved, which means that these issues need to be addressed before clinical trials can be considered.